2017
DOI: 10.1007/s10433-017-0439-y
|View full text |Cite
|
Sign up to set email alerts
|

The acute physiological effects of high- and low-velocity resistance exercise in older adults

Abstract: The aim of the present study was to determine if workload matched, high-velocity (HVE) and low-velocity (LVE) resistance exercise protocols, elicit differing acute physiological responses in older adults. Ten older adults completed three sets of eight exercises on six separate occasions (three HVE and three LVE sessions). Systolic blood pressure, diastolic blood pressure and blood lactate were measured pre-and post-exercise, heart rate was measured before exercise and following each set of each exercise. Final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Furthermore, training at a high-movement velocity with 40% of 1-RM for 12-14 repetitions has been shown to elicit similar improvements in strength and power, as training at a low movement velocity for 8-10 repetitions with 80% 1-RM (Sayers and Gibson 2014). Additionally, Richardson et al (2017) observed that ratings of perceived exertion were significantly greater in a group of older adults when training at 80% 1-RM at a low-movement velocity compared to 40% 1-RM at a high-movement velocity, even when total volume-load was matched. Therefore, if HVLL elicits comparable improvements in strength and functional performance to LVHL, while being perceived as less exerting, HVLL may be a preferential form of resistance exercise for the older population.…”
mentioning
confidence: 94%
“…Furthermore, training at a high-movement velocity with 40% of 1-RM for 12-14 repetitions has been shown to elicit similar improvements in strength and power, as training at a low movement velocity for 8-10 repetitions with 80% 1-RM (Sayers and Gibson 2014). Additionally, Richardson et al (2017) observed that ratings of perceived exertion were significantly greater in a group of older adults when training at 80% 1-RM at a low-movement velocity compared to 40% 1-RM at a high-movement velocity, even when total volume-load was matched. Therefore, if HVLL elicits comparable improvements in strength and functional performance to LVHL, while being perceived as less exerting, HVLL may be a preferential form of resistance exercise for the older population.…”
mentioning
confidence: 94%